Die Flexibilität des Wirtschaftsraumes: Vortrag anläßlich des Festkollegiums zur Feier des 65. Geburtstages von Theodor Kraus am 11. 12. 1959 - Otremba, Erich (ERDKUNDE, 1961)
n the modern world economy, with its infinitely inter woven mesh of inter-relationships, all countries are forced to re-adjust themselves to rapid economic changes. To hold their positions on the world market they have to fall in with or counteract economic developments in other countries. Thus economic geographical analyses of countries should take this fact into account and, to arrive at economic geographical value judgements, should, in the descriptions and interpretations of the economic conditions, not only look at the potentialities for a continuous increase of economic intensity on the basis of their own resources. It is at least as important to include in the investigations those characteristics and properties of countries and economic regions which facilitate their keeping pace with rapid changes of the economic structure and the abilities which allow them to cope with these changes without risk and endangerment of their substance. This ability of adjustment as regards economic development processes is termed flexibility. A physically and a socially conditioned flexibility may be distinguished. The concept of flexibility has been used in economic science for some time. It embraces the possibilities of an area to react according to its basic structure against exogenous tendencies of change, its natural multiplicity of potential utilisation, its security and lasting power for an economic life as varied as possible - and all this, without suffering irreparable disturbance or danger. In the second part of the paper this working concept is used in a few examples taken from different economic spheres to test whether it can be used successfully for the opening up of new ways of approach to arrive at a better understanding.